Effectiveness of guideline faecal indicator organism values in estimation of exposure risk at recreational coastal sites - Craig, D.L.; Fallowfield, H.J.; Cromar, N.J. (Water science and technology, 2003)
Decay rates in coastal water and sediment for the bacterial pathogens Salmonella typhimurium and S. derby were compared in laboratory-based microcosms with results previously obtained for a number of faecal indicators. In general, the decay rates of Salmonella spp. were greater than either enterococci or coliphage in overlying water and sediment. Decay rates of E. coli were similar to Salmonella spp. in overlying water, although greater in sediment. Raised temperature resulted in an increased decay rate for all organisms in the overlying water (and to a lesser extent in the surface sediment layer). It was demonstrated that decay rates for both S. typhimurium and S. derby were greater in overlying water compared with sediment. This suggested that sediments may be acting as a reservoir for pathogenic microorganisms released into the coastal environment during recreational activity and should be considered when estimating environmental exposure. Using measured decay rates and available dose-response data, a quantitative microbial risk assessment (QMRA) utilising Monte Carlo simulation was undertaken to estimate the risk of infection to Salmonella spp. following exposure to recreational coastal water subject to a range of faecal contamination levels. In waters of extremely poor quality, subject to contamination by faecal coliforms (106 CFU/100 mL), the maximum probability of infection on the day of an accidental release was above 2.0 × 10−1 and remained above 1 × 10−3 for three days following the initial high concentration.